Two-Phase CS0 for Introductory Programming: CS0 for CS1 - Naveed, Muhammad Shumail; Sarim, Muhammad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
Computer programming is the heart of computer science and thereby an important skill of the students. However, comprehending programming is extremely hard and introductory courses on programming are notorious to cause issues and challenges for learners, which affect their motivation and consequently cause high dropouts and low retention. This paper introduced CS0 as a precursor programming course to teach beginners, the fundamental notions of programming before the first course on programming. The proposed CS0 is grounded on two-phase learning strategy and equipped with a collaboration strategy. The results of the initial evaluation of proposed course are reasonably encouraging to motivate and prepare the novices for the first course on programming. The statistical significance of a proposed course is observed in improving the academic outcomes of novices in a first programming course. The normality of data was checked using the Kolmogorov-Smirnov and Shapiro-Wilk tests. The findings were analyzed with one-way ANOVA test and Kruskal–Wallis H test, indicating that the suggested course is statistically significant in enhancing the academic achievements of beginners in their first programming course.